Kesalahan Siswa dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel - Ade Ayu Dwiguningtyas; Betty Kusumaningrum; Denik Agustito; Istiqomah Istiqomah; Tri Astuti Arigiyati; Annis Deshinta Ayuningtyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
Students' errors in solving mathematical problems reflect their level of understanding and systematic thinking skills. This qualitative study aims to identify the types of errors and factors causing students' difficulties in solving the System of Linear Equations in Two Variables (SPLDV). The subjects were three eighth-grade junior high school students in Banjarnegara who were selected purposively. Data were obtained through written tests, in-depth interviews, and documentation. The results showed three main error categories: errors in modeling problems, calculations, and incomplete answer structures. The contributing factors include weak conceptual understanding, minimal contextual practice, the habit of solving problems instantly, and a lack of thorough problem interpretation. These findings are expected to provide an empirical basis for teachers and curriculum developers in designing effective learning and emphasizing conceptual understanding, contextual practice, reasoning, and systematic communication in SPLDV material